2017
DOI: 10.1145/3057889
|View full text |Cite
|
Sign up to set email alerts
|

Educational Game and Intelligent Tutoring System

Abstract: Educational games and intelligent tutoring systems (ITS) both support learning by doing, although often in different ways. The current classroom experiment compared a popular commercial game for equation solving, DragonBox and a research-based ITS, Lynnette with respect to desirable educational outcomes. The 190 participating 7th and 8th grade students were randomly assigned to work with either system for 5 class periods. We measured out-of-system transfer of lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(16 citation statements)
references
References 64 publications
0
16
0
Order By: Relevance
“…Many similar studies using DragonBox as a learning medium have been carried out, namely (Cates, 2018;Long & Aleven, 2017;Siew et al, 2016;Sylviani & Permana, 2020;Teofani et al, 2020). However, there has not been a single study that specifically uses the DragonBox puzzle game media combined with the DRM learning model to see its effect on students' concepts understanding skills and mathematical problem-solving skills.…”
Section: Picture 2 Dragonbox Algebra Puzzle Gamementioning
confidence: 99%
“…Many similar studies using DragonBox as a learning medium have been carried out, namely (Cates, 2018;Long & Aleven, 2017;Siew et al, 2016;Sylviani & Permana, 2020;Teofani et al, 2020). However, there has not been a single study that specifically uses the DragonBox puzzle game media combined with the DRM learning model to see its effect on students' concepts understanding skills and mathematical problem-solving skills.…”
Section: Picture 2 Dragonbox Algebra Puzzle Gamementioning
confidence: 99%
“…One of the main trends in education over the last decade has been the development of interactive environments that can be slowly introduced as part of the classroom or homework activities. Two of the most relevant tools for this purpose are Intelligent Tutoring Systems and Educational Games [41]. Most of the literature meta-reviews that have measured the effectiveness of such tools in the classroom [41,42] have reported positive effects.…”
Section: Intelligent Tutoring System In the Classroommentioning
confidence: 99%
“…Two of the most relevant tools for this purpose are Intelligent Tutoring Systems and Educational Games [41]. Most of the literature meta-reviews that have measured the effectiveness of such tools in the classroom [41,42] have reported positive effects. However, these studies also agree on the struggle that instructors face to effectively integrate these tools in their teaching and curriculum.…”
Section: Intelligent Tutoring System In the Classroommentioning
confidence: 99%
“…Various studies by Aleven and colleagues have confirmed that students engaging with Lynnette demonstrate clear learning gains as evidenced through increased performance from formal paper and pencil pre-tests to post-tests Aleven, 2014, 2017). However, Lynnette is still a prototype (Long and Aleven, 2017), albeit a promising one, and consequently the following figures in this section vary in their still developing layout.…”
Section: Cognitive Tutor: Lynnettementioning
confidence: 99%